2012
DOI: 10.1007/s10267-011-0155-y
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by Candida albicans on various prosthetic materials and its fluconazole sensitivity: a kinetic study

Abstract: Candida albicans has the ability to colonize various materials used in prostheses. In this report, we have studied the kinetics of biofilm formation on prosthetic materials and their susceptibility to fluconazole at various stages of development. Results indicated that C. albicans efficiently adheres to and colonizes polystyrene, polyvinylchloride, silicon, and polycarbonate surfaces. Candida albicans biofilm formation was observed to be both strainand substrate dependent. Adhesion of cells to solid substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
(40 reference statements)
0
28
0
Order By: Relevance
“…While, to analyze the effects on mature biofilms, medium with a range of drug concentrations was added to the 24 hour old biofilms. The plates were further incubated for 48 hours at 37 °C [23]. Density of the cells survived in biofilm forms was analyzed through metabolic activity in XTT-formazan reduction assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While, to analyze the effects on mature biofilms, medium with a range of drug concentrations was added to the 24 hour old biofilms. The plates were further incubated for 48 hours at 37 °C [23]. Density of the cells survived in biofilm forms was analyzed through metabolic activity in XTT-formazan reduction assay.…”
Section: Methodsmentioning
confidence: 99%
“…2, 3-bis (2-methoxy-4-nitro-sulfophenyl)-2H-tetrazolium-5-carboxanilide] (Sigma-Aldrich, India) reduction assay [23]. Briefly, XTT solution was prepared by mixing 1 mg/ml XTT salt in PBS and stored at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitization of Candida albicans biofilms to fluconazole by terpenoids of plant origin (Received February 19, 2014;Accepted June 19, 2014) Sonali DST-FIST and UGC-SAP School of Life Sciences, SRTM University, Nanded, 431606 (MS), India prescribed drug fluconazole (Shinde et al, 2012). Additionally, biofilms may act as reservoirs of infectious cells to cause re-infections (LaFleur et al, 2006).…”
Section: Full Papermentioning
confidence: 99%
“…Moreover, imaging of the biofilms using fluorescence microscopy revealed a heterogeneous structure, a network of extracellular matrix strands, characterized by the presence of yeast cells and hyphal forms. These Fungal infections, device-related biofilm infections caused by C. albicans in particular, had been linked with an increase use of medical device among immunocompromised patients or for surgical advances (Shinde et al, 2012). In 2015, it was reported that these caused 65% of infections in catheterized patients (Yousif et al, 2015).…”
Section: Discussionmentioning
confidence: 99%